2021
DOI: 10.3390/bioengineering8020024
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Electrospun Polycaprolactone-Polyaniline Scaffold Treated with Atmospheric Plasma to Improve Hydrophilicity

Abstract: Conductive polymers (CPs) have recently been applied in the development of scaffolds for tissue engineering applications in attempt to induce additional cues able to enhance tissue growth. Polyaniline (PANI) is one of the most widely studied CPs, but it requires to be blended with other polymers in order to be processed through conventional technologies. Here, we propose the fabrication of nanofibers based on a polycaprolactone (PCL)-PANI blend obtained using electrospinning technology. An extracellular matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…Viscosity and conductivity of the polymeric solution in electrospinning are two primary factors affecting the diameter of nanofibers 26 , 27 . It was shown that the addition of conductive PANI NPs increased the dielectric constant and thereupon the conductivity of the PCL solution 28 . The tension caused by the electric charges led to a decrease in the average diameter of the obtained PCL/PANI nanofibers 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscosity and conductivity of the polymeric solution in electrospinning are two primary factors affecting the diameter of nanofibers 26 , 27 . It was shown that the addition of conductive PANI NPs increased the dielectric constant and thereupon the conductivity of the PCL solution 28 . The tension caused by the electric charges led to a decrease in the average diameter of the obtained PCL/PANI nanofibers 28 .…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the addition of conductive PANI NPs increased the dielectric constant and thereupon the conductivity of the PCL solution 28 . The tension caused by the electric charges led to a decrease in the average diameter of the obtained PCL/PANI nanofibers 28 . For the samples with 3 and 5 wt.% PANI, fiber diameter was 238 ± 52 and 254 ± 85 nm, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma-based technology is quite efficient for the active control of polymer hydrophilicity and hydrophobicity, as evidenced by the above outlined examples. Moreover, extensive research efforts are currently underway to improve the efficiency and controllability of polymer wettability characteristics [ 88 , 89 ]. In addition to how surfaces interact with water, plasma treatment can be used to adjust oleophobicity.…”
Section: Plasma For Hydrophilicity and Hydrophobicity Control Of Polymersmentioning
confidence: 99%
“…Although this can somewhat be resolved by lowering the layer thickness, production time and cost will be severely affected. Another way to achieve better surface finish is by employing post-fabrication surface finishing, which can range from mechanical finishing (e.g., machining [ 219 ]) to chemical finishing (NaOH treatment [ 220 ], plasma etching [ 221 , 222 ]). In general, chemical finishing delivers a much more minute change compared to mechanical finishing, resulting in an ultra-smooth surface.…”
Section: Manufacturing Processmentioning
confidence: 99%